Geotechnical and Physico-Chemical Characterization of Low Lime Fly Ashes - Arif Ali Baig Moghal (Advances in Materials Science and Engineering)
In order to explore the possibility of using low-lime fly ashes, the physical and chemical properties which have a direct bearing on their geotechnical and geoenvironmental behaviors have been investigated. In this paper, two types of low-lime fly ashes, originating from India, have been used. A brief account of various methods adopted in characterizing their physical, chemical, and geotechnical properties is presented. The relative importance of each of these properties in enhancing the bulk applicability of fly ashes has been brought out.